Pediatric glioblastoma target-specific efficient delivery of gemcitabine across the blood–brain barrier via carbon nitride dots. Issue 14 (31st March 2020) - Liyanage, Piumi Y.; Zhou, Yiqun; Al-Youbi, Abdulrahman O.; Bashammakh, Abdulaziz S.; El-Shahawi, Mohammad S.; Vanni, Steven; Graham, Regina M.; Leblanc, Roger M.
Abstract : A carbon nitride dot nanocarrier system with effective drug conjugation and selective target delivering to achieve enhanced drug efficacy on pediatric glioblastomas, while proving capability to penetrate blood–brain barrier. Abstract : Pediatric glioblastomas are known to be one of the most dangerous and life-threatening cancers among many others regardless of the low number of cases reported. The major obstacles in the treatment of these tumors can be identified as the lack of prognosis data and the therapeutic requirement to be able to cross the blood–brain barrier (BBB). Due to this lack of data and techniques, pediatric patients could face drastic side effects over a long-time span even after survival. Therefore, in this study, the capability of non-toxic carbon nitride dots (CNDs) to selectively target pediatric glioblastoma cells was studied in vitro . Furthermore, the nanocarrier capability and efficiency of CNDs were also investigated through conjugation of a chemotherapeutic agent and transferrin (Tf ) protein. Gemcitabine (GM) was introduced into the system as a chemotherapeutic agent, which has never been successfully used for the treatment of any central nervous system (CNS) cancer. More than 95% of selective damage of SJGBM2 glioma cells was observed at 1 μM of CN–GM conjugate with almost 100% viability of non-cancerous HEK293 cells, although this ability was diminished at lower concentrations. However, further conjugation of Tf to obtain CN–GM–Tf allowed the achievement of selective targeting and prominent anti-cancer activity at a 100-fold lower concentration of 10 nM. Furthermore, both conjugates were capable of effectively damaging several other brain tumor cells, which were not well responsive towards the single treatment of GM. The capability of BBB penetration of the conjugates was observed using a zebrafish model, which confirms the CNDs' competence as an excellent nanocarrier to the CNS.